2016
DOI: 10.1159/000445572
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Promotes Myocardial I/R Injury by Increasing the Inflammatory Responses and Oxidative Stress Reactions

Abstract: Background/Aims: Inflammation and oxidative stress play an important role in myocardial ischemia and reperfusion (I/R) injury. We hypothesized that IL-23, a pro-inflammatory cytokine, could promote myocardial I/R injury by increasing the inflammatory response and oxidative stress. Methods: Male Sprague-Dawley rats were randomly assigned into sham operated control (SO) group, ischemia and reperfusion (I/R) group, (IL-23 + I/R) group and (anti-IL-23 + I/R) group. At 4 h after reperfusion, the serum concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 28 publications
2
36
0
1
Order By: Relevance
“…5B, troxerutin significantly increased p-Akt in H9c2 cells in a dose- and time-dependent manner. ROS release is thought to be important in the pathogenesis of myocardial I/R injury [27]. Our study found that the treatment of H9c2 cells with troxerutin markedly reduced H 2 O 2 -induced cell death compared to H 2 O 2 treatment alone.…”
Section: Resultssupporting
confidence: 48%
“…5B, troxerutin significantly increased p-Akt in H9c2 cells in a dose- and time-dependent manner. ROS release is thought to be important in the pathogenesis of myocardial I/R injury [27]. Our study found that the treatment of H9c2 cells with troxerutin markedly reduced H 2 O 2 -induced cell death compared to H 2 O 2 treatment alone.…”
Section: Resultssupporting
confidence: 48%
“…Thus, HMGB1, which serves as a promoter of the inflammatory responses, was recently discovered as pro-inflammatory cytokine [12]. TNF-α and IL-6 are the typical cytokines that could exacerbate IRI, thus it could be concluded that HMGB1 plays a pathogenic role in I/R, as illustrated by the up-regulation of HMGB1 and the generation of inflammatory factors in the kidney after I/R [31]. More importantly, in the I/R and HMGB1 groups, the levels of TNF-α, IL-6, IFN-γ and IL-1β were much lower in the TLR4 -/-mice than those in the WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress may play an etiological role in AMI and be useful as a biomarker [49]. When oxidative stress occurs, cells trigger a series of biochemical cascades to alter the redox balance and restore homeostasis following the development of atherosclerotic plaques and subsequent AMI [49].…”
Section: Com/cpbmentioning
confidence: 99%
“…When oxidative stress occurs, cells trigger a series of biochemical cascades to alter the redox balance and restore homeostasis following the development of atherosclerotic plaques and subsequent AMI [49]. During AMI, the miRNAs involved in inflammation may be indicators of the oxidative-stress response that maintains cellular homeostasis under ischemic and hypoxic conditions [50].…”
Section: Com/cpbmentioning
confidence: 99%